Theodore Boone : the activist - Grisham, John (New York, New York : Dutton Children's Books, an imprint of Penguin Group (USA) Inc., 2013)
"Aspiring lawyer Theodore Boone takes the stand to protect his political and environmental freedoms in the fourth installment of the series"--
Keywords: Lawyers -- Fiction; Courts -- Fiction; Political activists -- Fiction